Keunggulan Komparatif dan Kompetitif Komoditi Kopi Arabika (Coffea arabica) di Desa Ulian, Kecamatan Kintamani, Kabupaten Bangli - NI MADE METRI WIDHYAPURI; MADE ANTARA; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Comparative and Competitive Advantages of Arabica Coffee (Coffea arabica) Commodity in Ulian Village, Kintamani Sub-District of Bangli Regency The study aimed to analyze the comparative and competitive advantages and the divergence of input and output of arabica coffee commodity, to find out the government protection policy against inputs and outputs; and to investigate the impact of changes in input and output prices on profits, comparative advantages, competitive advantages, divergence, and government protection against inputs and outputs. Methods of data collection was interview and observation. The respondents were 38 farmers in Ulian Village, Kintamani, Bangli and selected by random sampling. Data analysis used Policy Analysis Matrix and sensitivity analysis. The result of analysis by using Policy Analysis Matrix showed that the social profit was Rp 47.953.373 and private profit of Rp 33.202.446. The superiority of arabica coffee commodity in Ulian Village consists of comparative and competitive advantages expressed in DRC ratio of 0.23 and PCR ratio of 0.29. The divergence of input and output consists of divergence of revenue of Rp15,734,996, tradable input divergence was Rp 0, domestic factor divergence was Rp. 994,070, and divergence of net profit of Rp 14,750,927. Government protection was expressed in NPCO ratio of 0.75, EPC ratio of 0.75, PC ratio of 0.69, and SRP ratio of -0.24. These ratios indicate that arabica coffee farmers in Ulian Village, Kintamani, Bangli have no protection from the government. Changes in input and output prices during inflation were at 3.02 percent, an increase in input prices by 10 percent and a fall in the price of output by 50 percent resulted in arabica coffee commodities in Ulian Village, Kintamani, Bangli to have comparative and competitive advantages. There is no government protection on arabica coffee farmers in Ulian Village, Kintamani Sub-District of Bangli Regency when input and output prices changed.